Estudo das etapas sintéticas de complexos mistos de ftalocianinas de zinco e cobalto com tetrafenilporfirina de zinco - Cordeiro, Márcia Regina (2004)
A systematic study of synthetic steps in the formation of phthalocyanine and porphyrin mixed complexes, having pyrazine as bridged ligand is described in this work. Two mixed complexes series were obtained, keeping constant the porphyrin metallic center and changing the metallic phthalocyanine, in order to investigate the effect of the metal ion in the final properties of these series. In all the stages the products were characterized by infrared and UV-vis. spectroscopies, thermal and elemental analysis. Thermogravimetric analysis have shown that pyrazine ligand does not influence zinc phthalocyanine(ZnPc), cobalt phthalocyanine(CoPc) or zinc tetraphenilporphrin(ZnTPP) thermal stability. However, the mass loss temperature of pyrazine ligand was dependent of metallic center in the phthalocyanine complex. The two mixed complexes series produced two different macrocycles sequence, ZnPc(pyz)ZnTPP(pyz)ZnPc; ZnTPP(pyz)ZnPc(pyz)ZnTPP; CoPc(pyz)ZnTPP(pyz)CoPc and ZnTPP(pyz)CoPc(pyz)ZnTPP. The infrared and electronic spectra showed characteristic absorption bands of the two macrocycles. However, the main features observed in the electronic spectra was a blue shift of 16 nm in the position of the Q band related to CoPc. This result indicates that the change of the metal ion at phthalocyanine complex can promote a more intense communication between the porphyrin and phthalocyanine ring. The change of metallic center has also change the thermal properties of the mixed complexes.